2006
DOI: 10.1111/j.1600-0781.2006.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin surface topography grading is a valid measure of skin photoaging

Abstract: Grading silicone impressions of skin surface topography is a highly reliable and a valid measure of photoaging and enables prediction of dermal elastosis in a population setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 16 publications
12
53
0
Order By: Relevance
“…This means that, for many of our participants, sunscreen use would have been uncommon during their childhood years, a time that appears particularly important for the development of skin damage. As with several other studies (12,28), age was an important predictor of skin damage, here measured by silicone casts. Our findings are very similar to those of Battistuta et al who found a 13% increase in the odds of higher cast score for every 1-year increase in age in a cohort of Queensland adults ages 18 to 79 years (12).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…This means that, for many of our participants, sunscreen use would have been uncommon during their childhood years, a time that appears particularly important for the development of skin damage. As with several other studies (12,28), age was an important predictor of skin damage, here measured by silicone casts. Our findings are very similar to those of Battistuta et al who found a 13% increase in the odds of higher cast score for every 1-year increase in age in a cohort of Queensland adults ages 18 to 79 years (12).…”
Section: Discussionmentioning
confidence: 78%
“…Silicone rubber casts of the back of the hand were taken as follows: a small amount of silicone liquid was mixed with catalyst and applied to the dorsum of the hand, avoiding major veins, visible skin blemishes, scars, etc. After 7 min, the cast was removed, allowed to dry, and stored in a labeled bag until grading (12). Silicone casts were graded by an independent grader who was blind to any other data on the participants.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations